2015
DOI: 10.1097/mpg.0000000000000742
|View full text |Cite
|
Sign up to set email alerts
|

Family Adjustment and Parenting Stress When an Infant Has Serious Liver Disease

Abstract: When parents report the presence of psychological symptoms, symptoms are likely to be present in both parents and are associated with difficulties adjusting to disrupted family roles. Father engagement may be protective of mothers' mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 21 publications
1
28
2
Order By: Relevance
“…Over a decade ago, mothers reported that their own mental health symptoms affect their ability to care for their children (Grupp-Phelan et al, 2003). Routine assessments of stress levels and changes in family roles and routines may be an important step in determining if caregivers could benefit from a referral to psychological services (Bowden et al, 2015). Screening questions to assess depressive symptoms in EDs or primary care practices have been recommended since 2008 by the American Academy of Pediatrics Task Force and the Bright Futures practice guidelines (Pak & Allen, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Over a decade ago, mothers reported that their own mental health symptoms affect their ability to care for their children (Grupp-Phelan et al, 2003). Routine assessments of stress levels and changes in family roles and routines may be an important step in determining if caregivers could benefit from a referral to psychological services (Bowden et al, 2015). Screening questions to assess depressive symptoms in EDs or primary care practices have been recommended since 2008 by the American Academy of Pediatrics Task Force and the Bright Futures practice guidelines (Pak & Allen, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Because only parents with the most contact with the child were asked to participate, it is possible that the fathers in this study were more engaged than the typical father. In a small study of parents of infants with liver disease, fathers who reported being highly engaged with the child expressed more anxiety about the child than did mothers [36]. Having more adults in the household to share the responsibilities of taking care of a child with RS may help the primary caregiver to adapt more successfully, possibly explaining that finding.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our results, Bowden et al reported comparable levels of psychological symptoms in parents of children with serious liver disease as in the general population. (27) However, Cabizuca et al described, in a systematic review with meta-analysis, that almost one in four parents of children with chronic diseasesuffer from post-traumatic stress disorder. (28) In our cohort, parents of school-aged children with BA reported comparable stress levels as the general population, whereas other studies reported elevated parental distress in parents of LTx recipients.…”
Section: Discussionmentioning
confidence: 99%